As entre(linhas) da psicanálise e da saúde mental: o cotidiano do trabalho com a práxis analítica - Carvalho, Débora Rocha (2024)
The analytical praxis in psychosocial care policies involves complex work, as it needs to grasp the multiple dimensions present in the daily activities of this practice. It requires an inventive capacity, working in coordination with different areas of knowledge, starting from an expanded understanding of the context and a perspective that comprehends the complexity of life in its infinite manifestations. Based on this, the present dissertation addresses an exploratory research with a qualitative approach, aiming to generate knowledge about the convergences and divergences between psychoanalysis and public policies on mental health and psychosocial care, from the perspective of psychoanalytically oriented professionals of the Sobral Comprehensive Mental Health Care Network (RAISM). The method used consisted of two procedures in two distinct stages: i) the use of an online form; ii) the use of the conversation circle technique with professionals who work from a psychoanalytical orientation in RAISM of Sobral. The analysis of the results, as well as the conduction of the conversation circle with the participants of this research, followed the methodological framework of psychoanalytic research. This research shed light, from the listening of the psychoanalytically oriented professionals of RAISM, on the movement of approaching and distancing and of knowing the possible methods of analytical praxis in the context of psychosocial care policies, demonstrating that this dynamic, between divergences and convergences, is part of the complex context that includes other discourses and knowledge. Regarding the convergences, how much analytical praxis adds and strengthens the construction of psychosocial care, especially in the way of understanding the subject and suffering, as well as in the relationship of the subject with themselves and in the social field. Regarding the divergences, when psychoanalysis as praxis operates in the field of mental health in a way that does not frame or correct the subject; instead, it produces a transference bond. Therefore, it is not functionalist and does not adapt to the interests of neoliberal policy. We conclude that it would not be the exclusion of divergences that could solve and give space to analytical work in an "effective" way, but rather, the importance of this tension, so that this movement incites reflection on praxis in institutions, exposing what psychoanalysis can add to these services, and vice versa, in constant construction.